The clove (Syzygium aromaticum) genome provides insights into the eugenol biosynthesis pathway - Sonia Ouadi; Nicolas Sierro; Simon Goepfert; Lucien Bovet; Gaetan Glauser; Armelle Vallat; Manuel C. Peitsch; Felix Kessler; Nikolai V. Ivanov (Communications Biology)
Abstract The clove (Syzygium aromaticum) is an important tropical spice crop in global trade. Evolving environmental pressures necessitate modern characterization and selection techniques that are currently inaccessible to clove growers owing to the scarcity of genomic and genetic information. Here, we present a 370-Mb high-quality chromosome-scale genome assembly for clove. Comparative genomic analysis between S. aromaticum and Eucalyptus grandis—both species of the Myrtaceae family—reveals good genome structure conservation and intrachromosomal rearrangements on seven of the eleven chromosomes. We report genes that belong to families involved in the biosynthesis of eugenol, the major bioactive component of clove products. On the basis of our transcriptomic and metabolomic findings, we propose a hypothetical scenario in which eugenol acetate plays a key role in high eugenol accumulation in clove leaves and buds. The clove genome is a new contribution to omics resources for the Myrtaceae family and an important tool for clove research.